2023
DOI: 10.1186/s40001-023-00998-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the accuracy of three intraocular lens power calculation formulas in cataract patients with prior radial keratotomy

Abstract: Purpose To compare the accuracy of three intraocular lens (IOL) formulas in Chinese cataract patients with prior radial keratotomy (RK). Methods Medical records of cataract patients with prior RK at Beijing Tongren Hospital were retrospectively analysed. The absolute error (AE) was calculated as the absolute difference between the actual postoperative spherical equivalent and the predicted spherical equivalent. The AE and percentages of eyes with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…They reported that Barrett True-K had MedAE 0.60 + 0.80 D and 0.69 + 0.67 D at 1 and >4 months postoperative, respectively. In a recent study, Li et al 20 compared the accuracy of Barrett True, Haigis, and DK Holladay 1 in Chinese cataract patients with that of a previous RK using standard K readings obtained from IOLMaster (similar to our study). They reported that the MedAE was lowest for the Barrett True-K formula (0.62), followed by Haigis (0.76), and DK Holladay 1 (1.16).…”
Section: Discussionsupporting
confidence: 68%
“…They reported that Barrett True-K had MedAE 0.60 + 0.80 D and 0.69 + 0.67 D at 1 and >4 months postoperative, respectively. In a recent study, Li et al 20 compared the accuracy of Barrett True, Haigis, and DK Holladay 1 in Chinese cataract patients with that of a previous RK using standard K readings obtained from IOLMaster (similar to our study). They reported that the MedAE was lowest for the Barrett True-K formula (0.62), followed by Haigis (0.76), and DK Holladay 1 (1.16).…”
Section: Discussionsupporting
confidence: 68%
“…Utilization of the Haigis formula revealed findings in the present study that were comparable to those of Wang et al [12], Leite de Pinho Tavares et al [9], and Li et al [8], but differed from Turnbull et al [29], with the latter achieving 69.2% of eyes within ± 0.50 D of the target range, 86.5% of eyes within ± 0.75 D of the target range, and 92.3% of eyes within ± 1 D of the target range. In the Turnbull et al study [29], the Haigis calculation was performed using both a standard approach and by using a -0.50 D offset on target refraction, based on a study performed by Geggel et al [35] who stated that it may be more accurate.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the suggested A-constants and SF constants were used by each lens' manufacturer. This resulted in an A-constant of 119.3 and SF of 1.96 for the TECNIS ZCB00 monofocal lens (Johnson & Johnson Vision, Irvine, CA, USA); an A-constant of 119.1 and SF of 1.85 for the enVista enhanced MX60E lens; and an A-constant of 118.7 and SF of 1.81 for the AcrySoft SN60WF lens [8][9][10][11]. A K-index value of 1.3375 was utilized where required [24][25][26].…”
Section: Formulasmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent study compared the accuracy of the Barrett True-K, Holladay 1 (D-K), and Haigis formulas for calculating IOL power, and the Barrett True-K formula was the most accurate in Chinese cataract patients with prior RK. However, even using the Barrett True-K formula, only 46.8% of eyes had an absolute error within 0.5 D (34). Thus, newer and more accurate IOL formulas are desired.…”
Section: Management Of Refractive Surprisesmentioning
confidence: 99%